HUBUNGAN MOTIVASI DAN ETOS KERJA DENGAN PENDAPATAN USAHA TERNAK ITIK PETELUR DI KECAMATAN MARGADANA KOTA TEGAL - Soffy Aldi DwiHarta; Krismiwati Muatip; Oentoeng Edy Djatmiko (ANGON: Journal of Animal Science and Technology, 2020)
Background. Motivation and work ethos are important for laying duck farmers because they are thought to affect the income of laying duck bussiness. This research be held on 7 December – 31 December 2019. This research aims are (1) to investigate the motivation of laying duck farmers in Margadana sub-district, (2) to investigate the work ethos of laying duck farmers in Margadana sub-district, (3) to investigate the bussiness income of laying duck farmers in Margadana sub-district, and (4) to analyze the relationship of motivation and work ethos with laying duck bussiness income in Margadana sub-district. The research method used was survey method. Materials and Methods. The method of sample area determined by using purposive sampling technic, 3 village were selected in Margadana sub-district, thats are Pesurungan Lor, Margadana, and Sumurpanggang. Respondent are taken by using random sampling technic many as 50 laying duck farmers. The analytical method used is descriptive analysis and spearman rank correlation analysis. Results. The results showed that laying duck farmers in Margadana sub-district had the motivation of laying duck farming in the medium category. The work ethos of laying duck farmers in Margadana sub district is still low. The Majority of laying duck farmers in Margadana sub-district have moderate income between Rp 1.828.692,00 – Rp 7.718.018,00 and the average income of laying duck farmers is Rp 4.773.355,00/month. Conclusion. Based on the result of the spearman rank analysis, motivation has a medium relationship category with the income of laying duck farmers, while the work ethos has a low relationship with the income of laying duck bussiness.